2021
DOI: 10.2147/dmso.s315471
|View full text |Cite
|
Sign up to set email alerts
|

Biochanin A Regulates Cholesterol Metabolism Further Delays the Progression of Nonalcoholic Fatty Liver Disease

Abstract: To discover the possible target of biochanin A (BCA) in the lipid metabolism pathway and further explore its mechanism to nonalcoholic fatty liver disease (NAFLD). Methods: We adopted a high-fat and high-glucose diet for 12 weeks to build the NAFLD rat model, which was then treated with different proportions of BCA for 4 weeks. General condition, body weight, Lee index, and liver index were then evaluated. Furthermore, blood lipid level and insulin resistance (IR) were detected. Moreover, hematoxylin and eosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Biochanin A ( C2 ), an O -methylated isoflavone belonging to the phytochemical class of flavonoids, has several pharmacological effects, including anti-inflammatory, lipid-lowering, and cholesterol-lowering effects as well as cancer chemoprevention-related effects [ 63 , 64 ]. In diabetic rats, biochanin A, as a potent activator of both PPAR-γ and PPAR-α receptors, has shown promising and interesting effects in lowering glycemia and improving insulin sensitivity [ 65 , 66 ].…”
Section: Future Direction For the Management Of The Diseasementioning
confidence: 99%
“…Biochanin A ( C2 ), an O -methylated isoflavone belonging to the phytochemical class of flavonoids, has several pharmacological effects, including anti-inflammatory, lipid-lowering, and cholesterol-lowering effects as well as cancer chemoprevention-related effects [ 63 , 64 ]. In diabetic rats, biochanin A, as a potent activator of both PPAR-γ and PPAR-α receptors, has shown promising and interesting effects in lowering glycemia and improving insulin sensitivity [ 65 , 66 ].…”
Section: Future Direction For the Management Of The Diseasementioning
confidence: 99%
“…By analysing the pancreatic tissue from BCA-treated/non-BCA-treated streptozotocin diabetic rats, it was found that the BCA-treated rats had reduced fat in normal pancreatic islet cells, indicating that BCA could act as a preventative measure against weight loss in diabetic animals (Figure 3) [22]. As a fatty acid amide hydrolase inhibitor, BCA can slow down the progression of nonalcoholic fatty liver disease (NAFLD) by regulating cholesterol metabolism [23,24]. BCA as a β-Site App-Cleaving Enzyme 1 (Bace1) inhibitor also has the potential to be developed into preventive and therapeutic agents for Alzheimer's disease [25].…”
Section: Physiological Functions Of Bcamentioning
confidence: 99%
“…In addition, IR, a possible pathogenesis of NAFLD, had positive correlation with the raised plasma levels of apoB48-containing lipoproteins, which might be due to impaired hepatic ability of clearing TG-rich lipoproteins caused by excessive production of intestinal chylomicrons (CMs) and accumulation of serum CM remnants [ 13 , 14 ]. On the other hand, cholesterol absorption is mainly accomplished by the endocytosis of exogenous cholesterol through peroxisome proliferator activated receptors (PPARs) and low-density lipoprotein receptor (LDL-R), while cholesterol excretion is through the bile acid pathway [ 15 ]. PPARs exist in a variety of tissues with active metabolism such as the liver and participate in regulating the absorption and metabolism of cholesterol, phospholipids, and FFAs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%